Pengaruh Mordan Tawas, Kapur Tohor dan Tunjung Terhadap Hasil Ecoprint Daun Bidara Laut (Ziziphus mauritiana L) pada Bahan Rayon Twill dengan Teknik Hammering - Farida Farida; Sri Zulfia Novrita; Ernawati Ernawati; Samuel Martin Pradana (LPPM Institut Seni Indonesia Padangpanjang, 2025)
This research is motivated by the development of ecoprint using natural materials so as to reduce the use of harmful synthetic substances. The purpose of this study is to describe the color name, clarity of the motif shape and color resistance to washing with soap produced from ecoprint of bidara laut leaves on rayon twill material with hammering technique using alum, calcium oxide and tunjung mordants. This research is an experimental research with the object of research rayon twill fabric given a motif of bidara laut leaves. The type of data in this study is primary data sourced from questionnaires. The data analysis technique uses the Friedman K-Related Sample test with SPSS version 30.0. The results of ecoprint without mordant, with alum, calcium oxide and tunjung mordant produce various colors. The results of the clarity of the motif shape without mordant is clear, alum mordant is clear, calcium oxide mordant is clear and tunjung mordant is quite clear. The results of color resistance to washing with soap without mordant changed, the alum changed slightly, the calcium oxide changed and the tunjung changed, the results of the Friedman K-Related Sample test from the clarity of the leaf motif shape were 0.001 <0.05. Meanwhile, the color fastness to washing with soap is 0.000 < 0.05. From these data, it can be concluded that there is a significant effect due to the use of alum, calcium oxide, and tunjung mordants on the clarity of the motif shape and color fastness to washing with soap produced from the ecoprint